2019
DOI: 10.21608/ejh.2018.5079.1022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silymarin versus Silymarin and Green Coffee Extract on Thioacetamide Induced Liver Injury in Adult Male Albino Rats (Histological and Immunohistochemical Study)

Abstract: Background: Thioacetamide (TAA) is a potent hepatotoxic agent used to induce liver toxicity in experimental animal models. Protective role of silymarin in liver intoxication was proved. Coffee is the most popular beverage used in the world. Consumption of green coffee bean extract has many benefits on health in general, and liver in particular. Aim of work: To evaluate the potential role of adding green coffee extract to silymarin in improving thioacetamide induced hepatic injury in rats. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(23 reference statements)
5
7
0
Order By: Relevance
“…One interesting observation in this study is that the consumption of green coffee methanol extract escorted by silymarin had a protective effect on oxidative stress (MDA(and antioxidant redox system. Also, our results showed that consumption of green coffee methanolic extract accompanied by silymarin causes a suppressive effect on oxidative stress and confirmed the findings of other authors showing the antioxidant power of green coffee [ 21 , 22 , 29 ]. Furthermore, oxidative DNA damage was decreased; and glutathione level and glutathione reductase activities were increased after consumption of green coffee [ 29 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…One interesting observation in this study is that the consumption of green coffee methanol extract escorted by silymarin had a protective effect on oxidative stress (MDA(and antioxidant redox system. Also, our results showed that consumption of green coffee methanolic extract accompanied by silymarin causes a suppressive effect on oxidative stress and confirmed the findings of other authors showing the antioxidant power of green coffee [ 21 , 22 , 29 ]. Furthermore, oxidative DNA damage was decreased; and glutathione level and glutathione reductase activities were increased after consumption of green coffee [ 29 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…The histopathology of the liver of the CCl 4 -induced hepatic toxicity group (G2) showed injured hepatic tissues that led to the significant elevation of these liver function parameters in serum. Also, the total protein (TP) level was reduced in the CCl 4 rats showing the pulverization in the quantity of hepatic cells, which may result in a diminished hepatic ability to synthesize proteins [ 6 , 7 , 29 ]. Whereas the administration of the green coffee methanolic extract, silymarin, or their combination significantly and advantageously improved serum levels of these liver function parameters approaching them to the negative control group levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations